MOVING BEYOND THE ABYSSAL LINE: THE POSSIBILITY OF EPISTEMIC JUSTICE IN THE ‘POST’- APARTHEID CONSTITUTIONALISM (The Pretoria Student Law Review, 2023)
In this article, I reflect on the idea of a ‘post’-apartheid South Africanconstitutionalism and the related and implicated notion ofTransformative Constitutionalism by emphasising its continued bondageto a colonial and apartheid past. In an effort to critically explore the‘post’-apartheid transformative constitutional framework, I examinethe endurance of colonialism as coloniality in the manner it hasunfolded in the South African context. This exploration involveshighlighting three constitutive elements of this endurance: linearhistoricism as observed in Hobbes’ social contract; the geography ofreason as theorised by Schmitt; and the lines within South Africansociety and knowledge systems as a result of what De Sousa Santos calls‘abyssal thinking’. Although the endurance of historical colonialism ascoloniality can be described in a number of ways, I deal with thesespecific constitutive elements in order to argue that the doctrine of transformation, which includes Transformative Constitutionalism, haslargely been ineffective in its attempt to eradicate coloniality as it hasfailed to achieve epistemic justice for the majority of (South) Africans.I conclude by suggesting that the doctrine of transformation and, assuch, Transformative Constitutionalism has served to further excludeand marginalise the knowledge of indigenous (South) African people inthe ‘post’-apartheid constitutional dispensation. The project oftransformation has sustained the abyssal line as it has been internalisedthrough coloniality. As such, the ‘post’-apartheid South Africandispensation remains divided by this line — essentially discardingindigenous (South) African people and their knowledge systems to theabyss. I further argue that the persistence of coloniality, sustained bythe abyssal line, requires a project of conceptual decolonisation ifcoloniality and epistemic injustice is to be undone. In this sense, a true(South) African dispensation may be disclosed.